MANAGEMENT OF MANDIBULAR THIRD MOLAR SURGERY TO PRESERVE PERIODONTAL HEALTH OF SECOND MOLAR - Elitsa G. Deliverska (Peytchinski Publishing, 2017)
Background: Extraction of impacted third molar violates surrounding soft and bony tissues. Various surgical approaches and surgical technics have an important impact on the periodontal health of the adjacent second molar. Purpose: The aim of this review is to analyse the causes that can affect postoperative periodontal outcomes for the mandibular second molars (LM2) adjacent to the impacted/ semi impacted mandibular third molars (LM3). Material and Methods: Electronic searches were conducted through the MEDLINE (PubMed), Scopus, etc. databases to screen all relevant articles published from inception to April 2017. Results: Different flap techniques had no significant impact on the probing depth reduction or on the clinical attachment level of LM2. Szmyd and paramarginal flap designs may be the most effective in reducing the probing depth after third molar surgery, and the envelope flap may be the least effective. Use of bone substitutes and guided tissue regeneration therapy has been proposed, to eliminate or prevent these periodontal defects, but there is still no consensus on their predictability or clinical benefit. Higher costs and the risk of postoperative inflammatory complications should also be taken into proper account, as with any surgical procedure. "Orthodontic extraction" is indicated for that impacted M3 that present a high risk of postoperative periodontal defects at the distal aspect of adjacent M2. Conclusion: Risk factors associated with bone loss following lower third molar extraction includes age, the direction of the eruption, preoperative bone defects, and resorbtion of the LM2 root surface. Prevention of such periodontal defects continues to challenge clinicians.